ANALYSIS OF THE IMPLEMENTATION OF PROJECT-BASED LEARNING IN HISTORY LEARNING ON THE THEME OF SOUTH SUMATRAN MALAY CULTURAL CROSSOVERS: ANALISIS IMPLEMENTASI PEMBELAJARAN SEJARAH BERBASIS PROJECT BASED LEARNING PADA TEMA SILANG BUDAYA MELAYU SUMATERA SELATAN - Hikmah Maulana Yahya; Dina Sri Nindiati; Eva Dina Chairunisa (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to describe the implementation of Project Based Learning (PjBL)-based history learning on the theme of South Sumatran Malay cultural crossovers at SMA PGRI 1 Palembang. The focus of the study includes learning planning, learning implementation, and students' learning experiences during project-based learning activities. This research employed a descriptive qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The research subjects were a history teacher and tenth-grade students of SMA PGRI 1 Palembang. The findings revealed that the learning plan was systematically prepared through the formulation of learning objectives, selection of learning materials, project activity design, and the utilization of learning media and resources relevant to the theme of South Sumatran Malay cultural crossovers. The learning implementation was conducted according to the stages of Project Based Learning, including introductory activities, project implementation, project presentation, and learning evaluation. The application of Project Based Learning encouraged students' active participation through discussions, information exploration, collaborative work, and project development activities. Furthermore, students gained more meaningful, contextual, and relevant learning experiences connected to their socio-cultural environment, which enhanced their understanding of historical materials as well as the values of tolerance, togetherness, and cultural diversity. Therefore, the implementation of Project Based Learning-based history learning on the theme of South Sumatran Malay cultural crossovers supports the creation of active, contextual, and meaningful history learning.